The family economic status and outcome of people with schizophrenia in Xinjin, Chengdu, China: 14-year follow-up study. (May 2017) - Ran, Mao-Sheng; Yang, Lawrence H; Liu, Yu-Jun; Huang, Debbie; Mao, Wen-Jun; Lin, Fu-Rong; Li, Jie; Chan, Cecilia Lai-Wan
Background: Little is known about whether family economic status might influence the long-term (e.g. over 10 years) outcome of persons with schizophrenia in the community. Aim: To examine the differences in outcome at 14-year follow-up of persons with schizophrenia from high versus low family economic status backgrounds in a Chinese rural area. Method: A prospective 14-year follow-up study was conducted in six townships in Xinjin County, Chengdu, China. All participants with schizophrenia ( n = 510) were identified in an epidemiological investigation of 123, 572 people aged 15 years and older and followed up from 1994 to 2008. Results: Individuals from low family economic status (<mean) in 1994 had significantly higher rate of homelessness (9.9%) and lower rate of survival (63.8%) in 2008 than those from high family economic status (⩾mean; 3.2% and 76.6%, respectively). Individuals from low family economic status had significantly lower rates of marriage and complete remission, higher mean scores on Positive and Negative Syndrome Scale (PANSS) and lower mean score on Global Assessment of Functioning (GAF) than those from high family economic status in 2008. The predictors of low family economic status of individuals in 2008 encompassed the baseline low family economic status, poor families' attitude toward the patient, younger age, older age of first onset and longer duration of illness. Conclusion: Low family economic status is a predictive factor of poor long-term outcome of persons with schizophrenia in the rural community. Individuals' family economic status should be considered in making mental health policy and providing community-based mental health services.